23 Factors associated with transition from stage B to stage C heart failure with preserved ejection fraction. (7th October 2015) - Kenny, C; O'Neill, L; O'Connell, E; O'Hanlon, R; McDonald, K
Abstract : Background: Progression from stage B (asymptomatic patients with structural changes) to stage C heart failure (HF) with preserved ejection fraction (HF-pEF) is associated with a poorer prognosis. The factors which are associated with this transition are poorly understood. Methods: We identified patients with stage B HF from our database of STOP-HF patients and stage C HF from our HF unit database. Progressors were identified in both databases. Patients were excluded if they had an EF of <50%, a history of ≥grade 3 regurgitant or stenotic valvular heart disease, were in atrial fibrillation at the time of most recent echocardiogram or if they had died. Differences between Stage B HF, Transitioners and Stage C HF were assessed using Wilcoxon/Chi-square/Fisher tests as appropriate. All differences were considered significant at alpha = 0.05 with Bonferroni correction. Results: We identified 609 patients with stage B HF-pEF, 103 with Stage C HF-pEF and 28 progressors. Significant baseline differences between the groups are shown in Table 1 . Briefly, patients who transitioned from B to C were older, had a greater baseline LAVi, higher baseline E/e, a higher baseline BNP and a greater baseline prevalence of atrial fibrillation. Conclusion: Patients who developed symptomatic heart failure with preserved ejection fraction had evidence of more advanced structural and functional abnormalities prior to developing symptoms. The transition to symptomatic heart failure may be prevented or delayed by targeting this cohort for intense risk factor modification measures.